The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18034/gdeb.v8i2.653
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral And Perceptual Models for Secure Data Analysis and Management

Abstract: The ability to monitor and forecast citizen behavior on a large scale developed to be a top target for governments subject to security and intelligence that are collective in the current worldwide culture where the web has become the primary medium for commerce and communication. Meanwhile, significant privacy-related issues have surfaced considering the innovative opportunities that artificial intelligence (AI) generates for collective behavior analysis when presented to governments as a way in which the gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…According to our study, teaching is the second most preferred area for graduates, and social recognition is the main reason for this. Several studies also have shown the same result (Matin et al, 2018;Kewalramani & Phillipson, 2019;Achar, 2019a). Women prefer teaching most because of a secured career, handsome salary, less workload, and they can spend much time with family members (Matin et al, 2018;Amin & Rahman, 2018;Kewalramani & Phillipson, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…According to our study, teaching is the second most preferred area for graduates, and social recognition is the main reason for this. Several studies also have shown the same result (Matin et al, 2018;Kewalramani & Phillipson, 2019;Achar, 2019a). Women prefer teaching most because of a secured career, handsome salary, less workload, and they can spend much time with family members (Matin et al, 2018;Amin & Rahman, 2018;Kewalramani & Phillipson, 2019).…”
Section: Discussionmentioning
confidence: 81%